Transformational Governance in Metropolitan Environments: Findings from a Collaborative Port Expansion Initiative - Campos, Fernando; Meek, Jack W. (Revista Científica Foz, 2022)
This research examines stakeholder experiences in a complex urban setting froma newly designed collaborative governance process. The conceptual framework of Innes and Booher (1999) is used to capture the process within a larger metropolitan environment in the infrastructure development initiative - the China Shipping Terminal Expansion - at the Port of Los Angeles, California. Preliminary results indicate that a more joined-up, collaborative and network governance has taken place by forging ties among cross-sector actors and producing differentiated governance outcomes. The Port of Los Angeles infrastructure development initiative process represents a significant influence on governance patterns and offers evidence of transforming stakeholder perceptions and actions in the governance process.